Determination and Application of Reasonable Levels for Highly Directional Long Boreholes in Deep Outburst Coal Seams. (5th July 2022) - Zhang, DangYu; Zhang, MinBo; Wang, LongKang; Zeng, RuiPing; Wang, JinBao
Abstract : In order to solve the problem that the gas in the upper corner is easy to exceed the limit in the mining process of the deep outburst coal seam. Based on the theory of "O-ring" and the distribution of stratigraphy in the field, the development law of mining fissures in the overlying rock layer during the workface retrieval was studied by combining theoretical calculation and FLAC3D numerical modeling. The research results show that the range of fissure development zone in 2913 working face is 14.2 to 33 m from the coal seam roof, and the high drilling arrangement can be in the stable rock layer of the roof. For siltstone-fine sandstone interaction stratum, measures such as opening branches to adjust the layer and lowering the casing to protect the hole wall can be taken to ensure the stability of the borehole and the smooth flow of gas extraction channels. Field application shows that the high directional long borehole has the advantages of long extension distance and wide coverage, the average value of extraction mix is 34.3 m 3 /min, and the average value of extraction pure is 0.4 mm 3 /min, which helps to prevent the gas overlimit in the upper corner during the workface recovery. The high directional long borehole has obvious economic and safety benefits over the traditional high hole and has important promotion value in coal mine gas management.